Sanksi bagi Pelaku Pembunuhan yang Menderita Gangguan Bipolar Perspektif Hukum Islam - Rahmat, Rahmat; Nuraeni Novira; M. Amirullah; Amelia, Amelia (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2021)
This study aimed to review and analyze appropriate sanction for murderer suffering from bipolar disorder based on the perspective of Islamic law. This research was qualitative descriptive research with library research methods and approaches such as: (1) normative theology (syar'i); (2) historical; and (3) religious psychology. The results showed that murder is an illegal act in Islam so that the culprit is punished severely. Murder committed by people with bipolar disorder according to the perspective of Islamic law is sanctioned qiá¹£Äá¹£ if the act of murder is carried out when the perpetrator is in normal circumstances, but if the act of murder occurs when bipolar disorder relapses on the perpetrator, then the sanction is a full right on the part of the victim's family to still ask for a fine (diat).